Cyanobacterial conversion of carbon dioxide to 2,3-butanediol - Oliver, John W. K. (National Academy of Sciences, 2013)
Conversion of CO(2) for the synthesis of chemicals by photosynthetic organisms is an attractive target for establishing independence from fossil reserves. However, synthetic pathway construction in cyanobacteria is still in its infancy compared with model fermentative organisms. Here we systematically developed the 2,3-butanediol (23BD) biosynthetic pathway in Synechococcus elongatus PCC7942 as a model system to establish design methods for efficient exogenous chemical production in cyanobacteria. We identified 23BD as a target chemical with low host toxicity, and designed an oxygen-insensitive, cofactor-matched biosynthetic pathway coupled with irreversible enzymatic steps to create a driving force toward the target. Production of 23BD from CO(2) reached 2.38 g/L, which is a significant increase for chemical production from exogenous pathways in cyanobacteria. This work demonstrates that developing strong design methods can continue to increase chemical production in cyanobacteria.